2022
DOI: 10.3390/cancers14143476
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling Reveals Clinical Associations in Response to Immune Therapy in Head and Neck Cancer

Abstract: Comprehensive genomic profiling (CGP) provides information regarding cancer-related genetic aberrations. However, its clinical utility in recurrent/metastatic head and neck cancer (R/M HNC) remains unknown. Additionally, predictive biomarkers for immune checkpoint inhibitors (ICIs) should be fully elucidated because of their low response rate. Here, we analyzed the clinical utility of CGP and identified predictive biomarkers that respond to ICIs in R/M HNC. We evaluated over 1100 cases of HNC using the nationw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…TMB was determined through NGS/WES sequencing analyses of tumor samples in all the studies, except one study [ 20 ] that also assessed peripheral blood samples (Additional file 1 : Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TMB was determined through NGS/WES sequencing analyses of tumor samples in all the studies, except one study [ 20 ] that also assessed peripheral blood samples (Additional file 1 : Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…The muts/exome values were not available. One study defined a high TMB value of 175.0 muts/exome based on a literature review [ 21 ], and two studies used a cut-off of 10.0 and 15.0 muts/Mb [ 20 , 28 ]. Three studies established cut-off values based on the median TMB, with calculated values of 5.0 [ 18 ], 6.71 [ 22 ], and 7.6 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of infiltrating T cells in the tumor containing interferon-gamma (IFN-γ) responsive genes, a key factor for PD-L1 expression in HNSCC, may enhance the efficacy of anti-PD-1 therapies [ 139 ]. Furthermore, CCND1 amplification is mostly associated with an unfavorable response to ICIs and an unfavorable prognosis in HNSCC [ 140 ].…”
Section: Discussion and Future Perspectives On Oral Cancer Immune The...mentioning
confidence: 99%
“…Activating mutations or amplifications of ERBB2 and NTRK3 were discovered in 20% and 5% of cases, respectively, despite the absence of NTRK3 fusion. In contrast to forms with CCNDI1 amplification, which were less responsive and had a poor prognosis, it was found that forms with a high tumor mutational burden responded better to this type of approach [62]. According to recent studies, the human immune system can be a valuable ally in the battle against cancer.…”
Section: Recurrent/metastatic Carcinoma Of Head and Neckmentioning
confidence: 99%